A NEW SPECIES OF CYRTOSPIRIFER (BRACHIOPODA) FROM THE MIDDLE DEVONIAN OF THE WESTERN SAHARA (NORTHWESTERN AFRICA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
A new species of Cyrtospirifer is described from the Middle to Upper Givetian of the Western Sahara (Northwest Africa). Cyrtospirifer tindoufensis new species differs in its smaller number and coarser medial and flank plications and equibiconvex shell profile from the other Givetian species of Cyrtospirifer that all occur in Europe and to which the new species probably gives rise. The new implications of the proposed phylogeny of the earliest cyrtospiriferids and their origin from the Western Sahara are discussed. The palaeogeographic distribution of the cyrtospiriferids during the Givetian and Frasnian is shown and its migration ways are described considering the global transgression and regression cycles.
Keywords: Cyrtospirifer; Brachiopoda; Phylogeny; Palaeobiogeography; Givetian; Devonian; Western Sahara